Representaciones sociales en la prensa radial de Latacunga en torno al fútbol femenino - Apugllón León, Marco Vinicio (2016)
The objet of this research is to transmit a radio segement, dealing with women´s soccer, practicing with the main gool like letting society know about this sport practiced by women, because of this, we have quoted many authors, who affirm in their writings that women can develop and thive in the various disciplines they choose to do. Many research methods were used, such a the inductive, deductive, methods as research tools. Like interviews and surveys, allowing us to carry out an investigation with statistics that will support the research, this way the percentage of people that agree with the proposal will be known, as well as letting us make an analisis of each of the questions that survey contains, and therefore the respective interpretation….